Acne treatment review and future perspectives. Issue 9 (26th July 2022) - Mohsin, Noreen; Hernandez, Loren E.; Martin, Mackenzie R.; Does, Ashley Vander; Nouri, Keyvan
Abstract: Acne affects approximately 9% of people worldwide and is the most common skin condition in the USA. There are abundant topical and oral treatment options available for patients with acne. First‐line agents include topical retinoids, azelaic acid, benzoyl peroxide, and combinations of these agents. For recalcitrant or more severe acne, oral medications, including oral antibiotics, isotretinoin, or hormonal therapy, may be considered. This review will also discuss the many advances being made in the treatment of acne vulgaris, from the development of microencapsulated medications to targeted treatments.